Finance and Inclusive Growth - Cournède, Boris (OECD Publishing, 2015)
Finance is a vital ingredient for economic growth, but there can also be too much of it. This study investigates what fifty years of data for OECD countries have to say about the role of the financial sector for economic growth and income inequality and draws policy implications. Over the past fifty years, credit by banks and other intermediaries to households and businesses has grown three times as fast as economic activity. In most OECD countries, further expansion is likely to slow rather than boost growth. The composition of finance matters for growth. More credit to the private sector slows growth in most OECD countries, but more stock market financing boosts growth. Credit is a stronger drag on growth when it goes to households rather than businesses. Financial expansion fuels greater income inequality because higher income people can benefit more from the greater availability of credit and because the sector pays high wages. Higher income people can and do borrow more, so that they can gain more than others from the investment opportunities that they identify. The financial sector pays wages which are above what employees with similar profiles earn in the rest of the economy. This premium is particularly large for top income earners. There is no trade-off between financial reform, growth and income equality in the long term. In the short term, measures to avoid accumulating too much credit can, however, restrain growth temporarily. A healthy contribution of the financial sector to inclusive growth requires strong capital buffers, measures to reduce explicit and implicit subsidies to toobig- to-fail financial institutions and tax reforms to promote neutrality between debt and equity financing
Keywords: Economics